Development and pilot-scale validation of a fuzzy-logic control system for optimization of methane production in fixed-bed reactors. (August 2018) - Robles, A.; Capson-Tojo, G.; Ruano, M.V.; Latrille, E.; Steyer, J.-P.
Graphical abstract: Highlights: A fuzzy-logic control system for optimizing the methane production was proposed. The controller was developed, tuned and validated at a 350 L pilot-scale system. The controller aimed to maximize methane production whilst controlling VFA contents. Methane yields up to 0.29 L CH4 g −1 COD were achieved when running the controller. Abstract: The objective of this study was to develop an advanced control system for optimizing the performance of fixed-bed anaerobic reactors. The controller aimed at maximizing the bio-methane production whilst controlling the volatile fatty acids content in the effluent. For this purpose, a fuzzy-logic controller was developed, tuned and validated in an anaerobic fixed-bed reactor at pilot scale (350 L) treating raw winery wastewater. The results showed that the controller was able to adequately optimize the process performance, maximizing the methane production in terms of methane flow rate, resulting in an average methane yield of about 0.29 LCH4 g −1 COD. On the other hand, the controller maintained the volatile fatty acids content in the effluent close to the established maximum limit (750 mg COD L −1 ). The outcomes of this study are expected to facilitate plant engineers to establish an optimal control strategy that enables an adequate process performance with the maximum bio-methane productivity.